Uji Performa Model Batam Marine Ambulance Sebagai Armada Pendukung Medis dan Logistik - Naufal Abdurrahman Prasetyo; Rahman Hakim; Sapto Wiratno Satoto; Muliawan Nur Abiyad; Yogantara (Infotekmesin, 2023)
This study aims to test the performance of the Batam Marine Ambulance model as a medical and logistics support fleet using the comparison ship method. A series of stability and motion analysis processes were carried out, then the results were assessed to determine the best design among the proposed design options. Performance tests used three ship models (Model I, Model II, and Model III). It is known that in the stability test, the tilt angle of model III is 33.63° and the maximum GZ value is 4.673 cm. Then, in the resistance test, Model I has a lower resistance of 87.29 N and the required power is 1496.93 W compared to the other proposed models. In the seakeeping test, Model III was found to be more stable or less affected on all surface conditions because the RAO value was relatively lower, namely 90o in terms of heaving, rolling, and pitching at 135o and 180o then had lower additional resistance. The Model III design has good ship stability, drag, and seakeeping characteristics.